PROMOTING SNIPS STRATEGY TO FOSTER STUDENTS READING COMPREHENSION AT SMP XAVERIUS 2 PALEMBANG - Elfrida Harianja (Universitas Tridinanti Palembang, 2021)
The SNIPS strategy offers simple steps of reading activity by formulating the previous knowledge, interesting things in a text to help students comprehend and conclude the text. The objective of the study was to find out whether or not there was any significant difference in students’ reading comprehension of narrative text between the eighth grade students who were taught by using SNIPS strategy and those who were not. In conducting the study, the writer applied the experimental method by using quasi-experimental design. This design consisted of experimental and control groups. The VIII.B class became the control group and VIII.C became the experimental group. The two classes were chosen using purposive sampling technique and by considering they had the same level and problem of competency in learning English. Reading comprehension test was the instrument for collecting the data that was administered twice, the pre-test and post-test. The result showed that SNIPS strategy had a significant difference in the students’ reading comprehension. Based on the independent sample t-test analysis, it was found that the significant level was 0.000<0.05. It indicated that there was any significant difference in students’ reading comprehension in narrative text between the eighth grade students who were taught by using SNIPS strategy and those who were not. Keywords: Reading comprehension, SNIPS strategy